From Instruction to Inspiration: Pedagogical Approaches for Teaching in Private Music Education - Piter Sembiring; Al Muqri; Asep Rizwan Nurfalah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores pedagogical approaches in private music education, focusing on their impact on students' musical, cognitive, and emotional development. Using a qualitative approach, the study emphasizes the importance of individualized instruction, parental involvement, and technology integration. Observations and interviews conducted at Favore Music Bandung and GJKI Bandung Raya Church reveal that a flexible, student-centered approach, combined with motivational strategies, can significantly enhance engagement and creativity. Specifically, students showed increased creativity and motivation by selecting their favorite songs, which strengthened their emotional connection to music. Moreover, the integration of technology, including interactive music apps, enabled real-time feedback that enhanced students' technical skills and overall learning experience. Despite challenges such as limited teaching time and students busy schedules, the study suggests that a personalized learning model, focused on students' interests, effectively overcomes these obstacles. This paper concludes that adaptive pedagogical methods are essential for fostering holistic development, with further research needed to explore technology's broader application.